FAKTOR DOMINAN PENERAPAN SMKK PADA PROYEK PEMBANGUNAN PASAR RAYA KOTA PADANG - Rizki, Hardina; Carlo, Nafryzal; Heldi, Heldi (Rang Teknik Journal, 2025)
The Construction Safety Management System (CSMS) is a system designed to ensure safety in the execution of construction projects. This study aims to identify the factors influencing CSMS implementation (X) and analyze the dominant factors affecting project performance, measured by quality improvement (Y1), time reduction (Y2), and cost reduction related to work-related incidents or illnesses (Y3). The research employs a quantitative method, collecting data through observation and questionnaires distributed to stakeholders involved in the Pasar Raya Kota Padang construction project. Out of 113 questionnaires distributed, 91 were analyzed using SPSS version 26. The results reveal that from the initial 40 variables, five new factors were formed, comprising 26 variables that influence project performance. The most dominant factor is Responsibility, Management, and Compliance with Construction Safety (X1), which significantly impacts Y1 (t-value 12.494 t-table 1.99773), Y2 (t-value 10.054 t-table 1.99773), and Y3 (t-value 9.218 t-table 1.99773). In conclusion, X1 plays a crucial role in improving quality, reducing time, and minimizing costs associated with work-related incidents in the Pasar Raya Kota Padang construction project.Keywords: Construction Safety Management System, Implementation, Project Performance